OC-121 Fibroblast activation in the tumour microenvironment promotes tumour cell invasion and resistance to chemotherapy in oesophageal adenocarcinoma. (28th May 2012) - Hayden, A L; Derouet, M F; Noble, F; Primrose, J N; Blaydes, J P; Thomas, G; Underwood, T J
Abstract : Introduction: Stromal and other non-malignant cells have the potential to undergo modifications that can synergistically create a supportive microenvironment for tumour growth, invasion and metastasis. Oesophageal adenocarcinoma (EAC) is characterised by early invasion, leading to metastatic disease and therefore only 20% of patients are suitable for treatment with curative intent. Cancer associated fibroblasts (CAFs) have an activated, myofibroblastic phenotype and have been recognised as mediators of tumour progression in a range of solid tumours. This study investigates the role of CAFs in EAC invasion and resistance to chemotherapy. Methods: Functional biological analyses comparing primary fibroblasts from tumour stroma (CAF) and normal oesophagus (NOF) were carried out using organotypic culture, transwell invasion assays, collagen-1 gel contraction assays, siRNA gene silencing and colony forming assays. T-Tests (>95% CI) were carried out for all statistical analyses. Results: Primary oesophageal CAFs displayed an activated phenotype as demonstrated by α-SMA expression and increased collagen-1 gel contraction in comparison to NOFs (p<0.01). CAF conditioned medium supported tumour colony formation in the presence of cisplatin and 5-Fluorouracil compared to NOF conditioned medium (p<0.05). Ex vivo analysis revealed a twofold (p<0.05) increase in EAC cell invasion in response to primary (CAF) conditioned medium in transwell invasion assays that was replicated in 3D organotypic models containing co-cultures of fibroblasts and EAC tumour cells. Down-regulation of the CAF secreted molecule Periostin (PN) resulted in a 70% reduction in tumour cell invasion in transwell assays (p<0.05), and a total loss of invasion in organotypic culture. Furthermore, collagen-1 gel contraction was abrogated by PN down-regulation. NOFs exposed to TGF-β from 72 h demonstrate features of myofibroblastic activation including, PN expression and the ability to support increased EAC tumour cell invasion (p<0.05). Conclusion: This study has demonstrated that oesophageal derived primary CAF protect EAC cells from chemotherapy and promote tumour cell invasion. Increased α-SMA expression and collagen-1 gel contraction indicates CAF have a myofibroblast like phenotype. PN siRNA reduced gel contraction supports a hypothesis of autocrine regulation of the myofibroblast phenotype. Therefore targeting pathways that determine fibroblast activation may offer a novel therapy for preventing oesophageal cancer invasion and metastasis. Competing interests: None declared.